Crumple zone effect of nasal cavity and paranasal sinuses on posterior cranial fossa. (27th June 2014) - Lee, Thomas S.; Kellman, Robert; Darling, Andrew
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Examine a protective crumple zone effect of paranasal sinuses and nasal cavity on skull base fractures. Study Design Randomized‐control, cadaveric study. Methods In the experimental group (n = 4), the nasal cavity and bilateral sinuses of cadavers were obliterated with bone cement, whereas the control group (n = 4) had native sinus architecture. Increasing frontal, glabellar impacts were introduced. Each impact event was examined with a high‐speed video camera and sphenoid sinus pressure sensor. After each impact, computed tomography scans were performed and fracture sites were analyzed. Results The control group with intact sinuses showed statistically longer time duration, during which kinetic energy transfer occurred, and longer sphenoid wall pressure equilibrium time after an impact (P < 0.05). In the experimental group, there were statistically higher fracture incidences of clivus, petrous portion of internal carotid, occipital bone, and foramen magnum (P < 0.05). The type A pattern (n = 6) had anterior skull base failure occurring before posterior skull base failure. Type B pattern (n = 2), seen only in two experimental specimens, is marked by premature posterior skull base collapse occurring before anterior skull base failure with grossly disrupted posterior cranial fossa structures. Conclusion The presence of nasal cavity and paranasal sinuses behaves as a crumple zone to protect the cranial structures, preferentially posterior cranial fossa. Obliteration of the nasal cavity and paranasal sinuses with bone cement significantly increased structural tolerance of the anterior cranial vault to frontal, glabellar impacts at the cost of premature, posterior cranial fossa failure. Level of Evidence N/A. Laryngoscope 124:2241–2246, 2014